Characteristic spanwise length scales of streamwise vortical structures in the wake of a circular cylinder at Re = 1500 measured via global and local approaches. (30th January 2023) - Sarwar, Wasim; Mansy, Reda El; Bergadà, Josep M.; Mellibovsky, Fernando
Abstract: Wake characteristics of the flow past a circular cylinder are analysed in detail at Reynolds number Re = 1500 via direct numerical simulation. A periodic spanwise domain of length 1 . 5 π D has been found to yield correct first- and second-order wake statistics in remarkable agreement with published results at the same and closeby Re . A Kelvin–Helmholtz instability with a frequency f KH ≃ 0 . 666 is observed to occur intermittently in the shear layers issued from the top and bottom of the cylinder. The three-dimensional patterns in the wake have an estimated spanwise length scale l z 1 / D ≃ 0 . 70 (D is the cylinder diameter) in the near-wake at ( x, y ) / D = ( 3, 0 . 5 ), downstream from the cylinder, when quantified by autocorrelation (global approach). When using the Hilbert-transform (local approach) instead, the predicted length scale of streamwise vortical structures is distributed around λ z / D ≃ 0 . 33 at the same sampling location. Our results show that the two approaches measure different aspects of three-dimensionality: while the former informs of the typical spanwise spacing of streamwise vortices, the latter quantifies the local spanwise size of these same flow structures. Highlights: Streamwise vortices in the wake past a circular cylinder have been measured Vortices are strongest on the braids connecting consecutive Kármán vortices The streamwise vortices are characterised by two distinct spanwise length scales The two length scales measure different spatial aspects of the vortices The smallest length scale quantifies the typical spanwise size The largest length scale is related to the preferred spanwise spacing